How should we measure informed choice? The case of cancer screening. Issue 4 (30th March 2005) - Jepson, R G; Hewison, J; Thompson, A G H; Weller, D
Abstract : Informed choice is increasingly recognised as important in supporting patient autonomy and ensuring that people are neither deceived nor coerced. In cancer screening the emphasis has shifted away from just promoting the benefits of screening to providing comprehensive information to enable people to make an informed choice. Cancer screening programmes in the UK now have policies in place which state that it is their responsibility to ensure that individuals are making an individual informed choice. There is a need to evaluate whether such policies mean that those people invited for screening are making informed choices, and how comprehensive information affects other variables such as uptake, cost effectiveness, and satisfaction. At the present time, there is no validated measure of informed choice in cancer screening. Such a measure could be used to evaluate the effectiveness of interventions to increase informed choice and levels of informed choice in a population invited for screening. It could encourage health professionals to be accountable. Factors important when measuring informed choice in cancer screening include an individual's understanding of the limitations of screening, the ability to make an autonomous choice, and the difference between choice and behaviour.